The impact of diaphragmatic breathing exercises combined with facial cold stimulation on dyspnea perception, respiratory rate, and peak expiratory flow in COPD patients - Rustam Ali; Novita Ana Anggraini; Yuly Peristiowati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) represents a significant global health burden, contributing substantially to long-term morbidity and mortality rates worldwide. Purpose: To evaluate the effectiveness of diaphragmatic breathing exercises combined with facial cold stimulation on dyspnea perception, respiratory rate, and peak expiratory flow in COPD patients. Method: A quasi-experimental study was conducted using a pre-test and post-test control group design, involving 46 participants divided into intervention and control groups. Data collection tools included questionnaires, respiratory rate observations, and a peak flow meter. For data analysis, inferential statistics were applied: the Independent t-test and Paired t-test were used for normally distributed ratio data, while the Wilcoxon Signed Ranks Test and Mann-Whitney U Test were employed for ordinal data. Results: The combination of diaphragm breathing exercises and cold facial stimulation significantly reduces dyspnea perception in COPD patients. This intervention was also found to be effective in lowering the respiratory rate of COPD patients. Additionally, the results revealed a significant improvement in Peak Expiratory Flow Rate (PEFR) in the intervention group compared to the control group. Conclusion: Peak Expiratory Flow Rate (PEFR) significantly improved in the intervention group compared to the control group, indicating the combined intervention's efficacy in enhancing respiratory function in COPD patients.